Effect of a multifaceted intervention on number of antimicrobial prescriptions for suspected urinary tract infections in residents of nursing homes: cluster randomised controlled trial. Issue 7518 (8th September 2005) - Loeb, Mark; Brazil, Kevin; Lohfeld, Lynne; McGeer, Allison; Simor, Andrew; Stevenson, Kurt; Zoutman, Dick; Smith, Stephanie; Liu, Xiwu; Walter, Stephen D
Abstract: Objective To assess whether a multifaceted intervention can reduce the number of prescriptions for antimicrobials for suspected urinary tract infections in residents of nursing homes. Design Cluster randomised controlled trial. Setting 24 nursing homes in Ontario, Canada, and Idaho, United States. Participants 12 nursing homes allocated to a multifaceted intervention and 12 allocated to usual care. Outcomes were measured in 4217 residents. Interventions Diagnostic and treatment algorithm for urinary tract infections implemented at the nursing home level using a multifaceted approach—small group interactive sessions for nurses, videotapes, written material, outreach visits, and one on one interviews with physicians. Main outcome measures Number of antimicrobials prescribed for suspected urinary tract infections, total use of antimicrobials, admissions to hospital, and deaths. Results Fewer courses of antimicrobials for suspected urinary tract infections per 1000 resident days were prescribed in the intervention nursing homes than in the usual care homes (1.17 v 1.59 courses; weighted mean difference −0.49, 95% confidence intervals −0.93 to −0.06). Antimicrobials for suspected urinary tract infection represented 28.4% of all courses of drugs prescribed in the intervention nursing homes compared with 38.6% prescribed in the usual care homes (weighted mean difference −9.6%, −16.9% to −2.4%). The difference in total antimicrobial use per 1000 resident days between intervention and usual care groups was not significantly different (3.52 v 3.93; weighted mean difference −0.37, −1.17 to 0.44). No significant difference was found in admissions to hospital or mortality between the study arms. Conclusion A multifaceted intervention using algorithms can reduce the number of antimicrobial prescriptions for suspected urinary tract infections in residents of nursing homes.